2016
DOI: 10.1016/j.devcel.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

KIF1A/UNC-104 Transports ATG-9 to Regulate Neurodevelopment and Autophagy at Synapses

Abstract: SUMMARY Autophagy is a cellular degradation process essential for neuronal development and survival. Neurons are highly polarized cells in which autophagosome biogenesis is spatially compartmentalized. The mechanisms and physiological importance of this spatial compartmentalization of autophagy in the neuronal development of living animals are not well understood. Here we determine that, in C. elegans neurons, autophagosomes form near synapses and are required for neurodevelopment. We first determine, through … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 120 publications
(226 reference statements)
5
119
0
Order By: Relevance
“…In addition to protecting the viability of mature neurons, autophagy may also play an important role in the development of the nervous system (Fimia et al, ; Tang et al, ; Dragich et al, ; Stavoe et al, ). Autophagy has been implicated early in neurodevelopment during formation of the neural tube (Fimia et al, ).…”
Section: Autophagy In Development Of the Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to protecting the viability of mature neurons, autophagy may also play an important role in the development of the nervous system (Fimia et al, ; Tang et al, ; Dragich et al, ; Stavoe et al, ). Autophagy has been implicated early in neurodevelopment during formation of the neural tube (Fimia et al, ).…”
Section: Autophagy In Development Of the Nervous Systemmentioning
confidence: 99%
“…Curiously, while Atg9‐deficient neurons show defects in neurite outgrowth in vitro , Atg7‐deficient neurons do not exhibit defects in neurite outgrowth, (Yamaguchi et al, ), raising the possibility of autophagy‐independent roles for autophagy genes, such as Atg9, during brain development. In some conditions, autophagy may function as a negative regulator of axon outgrowth with reduced autophagy levels resulting in increased axon length (Ban et al, ; Stavoe et al, ). Although the precise mechanisms underlying the contributions of autophagy in axonal growth and guidance are unknown, autophagy in the leading edge of the axon may facilitate membrane recycling or turnover of signaling information in the migrating growth cone.…”
Section: Autophagy In Development Of the Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that ATG9-containing vesicles can localize to the ends of the axons, near presynaptic regions, in an UNC-104/KIF1A-dependent manner [88]. Direct interference of ATG-9/ATG9 transport results in a dramatic reduction of autophagosome biogenesis in these developing neurons [88]. How other ATG proteins are delivered to these sites remains to be discovered.…”
Section: Autophagy In Neuronsmentioning
confidence: 99%
“…We also discovered a role for autophagy in synapse formation (Stavoe et al , 2016) and documented a metabolic subcompartment that powers synaptic function and animal behavior (Jang et al , 2016). All of our projects started by asking simple, fundamental questions, understanding how to break them down into solvable experimental problems and pioneering new approaches, by forging collaborations, that provide tractable ways of addressing our questions.…”
Section: Maturation and Pruningmentioning
confidence: 99%